Website Media Recontruction for Basketball Learning Using Visual Studio Code Application - Muhammad Revan Hermansyah; Silvy Juditya; Mamat Heryanto (Journal of Physical and Outdoor Education, 2026)
This study aims to determine the process of reconstruction of learning media in the form of a website in the material of basketball games using the Visual Studio Code application for class X Marketing 1 students of SMKN 11 Bandung. The method used is the ADDIE development method which consists of five stages, namely Analyze, Design, Develop, Implement, and Evaluate. The subjects of this study involved three experts, namely material experts, media experts, and practitioners/teachers, as well as 33 students of class X Marketing 1 as learners through total sampling technique. The research instrument consists of a questionnaire feasibility for experts and pretest and posttest for students. The data analysis technique used percentage test for product feasibility and Wilcoxon Signed-Rank Test for learning effectiveness through SPSS 25. The feasibility test results from the three experts showed an average percentage of 87.11% which is included in the "Very Feasible" category. In addition, the results of the pretest and posttest showed an increase instudent learning outcomes, with an average pretest of 71.71 and an average posttest of 87.06. These results indicate that the website learning media that has been developed is effective in increasing students' understanding of basketball game material.